AN ANALYSIS OF THE EFFECTS OF RISK MANAGEMENT PROCESSES ON SUPPLY CHAIN PERFORMANCE IN THE INSURANCE INDUSTRY IN KENYA (A CASE OF KENYA REINSURANCE CORPORATION LIMITED) - SIGILAI, JENIFFER CHEPKOECH (IJRDO - Journal of Business Management, 2015)
Risk Management is defined in the standard (AS/NZS 4360:2004) as the systematic application of management policies, procedures and practices to the tasks of establishing the context, identifying, analysing, assessing, treating, monitoring and communicating. This study sought to find out the effects of risk management process on supply chain performance in insurance industry having Kenya Re as its case study. The main factors that was examined include; monitoring, business planning, resource allocation and risk reduction. The methodology of this study was purely qualitative. The study adopted stratified sampling to pick the respondents from a target population of 105 employees at the Kenya Re, Nairobi office. Data was obtained through primary data sources by means of face to face interviews guided by questionnaires administered to a selected sample. A total of 32 employees sampled from different departments formed the respondents of this study. The questionnaires was administered through drop and pick later method to the respondents. Once collected, the data was presented using tables and figures. Findings from the study revealed that the highest predictor for Supply Chain Performance is Risk Resource allocation with a beta value of 0.635 followed by Risk Planning with a beta value of 0.548 then Risk Reduction with a beta value of 0.355. Risk Monitoring is the least predictor of Supply Chain Performance with a beta value of 0.323. The study concludes that risk planning is very essential in supply chain performance since it reduces possible supply chain risks. This is bearing in mind that results from monitoring should be used in controls the study also concludes that risk planning indeed reduces disruptions in supply chain and thus mitigates risks in the supply chain which is an essential variable in supply chain performance. The study recommends that In order to ensure that the resources allocation process is efficient; the players in the insurance industry should engage a broad range of stakeholders in order to ensure that the process is reasonable and they are accountable. The study recommends further research on the compatibility of risk management and business process management, including the ability to minimize risks in business processes by design and to mitigate such risks at run time.